2011
DOI: 10.1002/adfm.201002497
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Pairing for De Novo Design of Self‐Assembling Peptides and Their Drug Delivery Potential

Abstract: Molecular self-assembly has emerged as the "bottom-up" engineering route to fabricate functional supramolecules for diverse applications. The design of molecular building units becomes critical in determining the structure, properties, and function of the resulting assemblies. Here, a de novo design principle of amino acid pairing (AAP) to generate new classes of self-assembling peptides (SAPs) is presented. In this study, the AAP focuses on hydrogen bonding, and ionic and hydrophobic interactions among amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
59
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 39 publications
1
59
0
1
Order By: Relevance
“…However, modifying α-helical based self-assembling peptides without disrupting the self-assembly process poses greater difficulties, but noncovalent functionalization with peptide tags offers a possible route to rendering this class of peptide hydrogels bioactive. [91,92] It is also still a challenge to be able to design various molecules that assemble in a predictive manner to a wide range of desired structures, although rational design of supramolecular structures are steps toward that direction [93,94] In addition, while the use of self-assembling peptides have largely been limited to soft tissue engineering, the development of hydrid systems may offer an interesting avenue in expanding their application. Finally, solid-state synthesis of peptides may be efficient for small scale production, but its scale up can be expensive.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…However, modifying α-helical based self-assembling peptides without disrupting the self-assembly process poses greater difficulties, but noncovalent functionalization with peptide tags offers a possible route to rendering this class of peptide hydrogels bioactive. [91,92] It is also still a challenge to be able to design various molecules that assemble in a predictive manner to a wide range of desired structures, although rational design of supramolecular structures are steps toward that direction [93,94] In addition, while the use of self-assembling peptides have largely been limited to soft tissue engineering, the development of hydrid systems may offer an interesting avenue in expanding their application. Finally, solid-state synthesis of peptides may be efficient for small scale production, but its scale up can be expensive.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…Here, the hydrophobic residues encapsulated and stabilised hydrophobic drugs and enhanced selfassociation of the peptide. Additionally, hydrogen bonds were found to stabilise peptide assemblies with charged residues, increasing the solubility of the peptide [87]. It has been shown that EAK16-II (AEAEAKAKAEAEAKAK) and EAK16-IV (AEAEAEAEAKAKAKAK) have different charge distributions creating stabilized hydrophobic compounds in aqueous solutions and releasing them into the cell in a controlled manner.…”
Section: Amino Acid Pairingmentioning
confidence: 97%
“…Hydrogel scaffold composed of alternating hydrophilic and hydrophobic residues and clusters of negative and positive charges on the N-and C-terminus, respectively. Adapted from [87].…”
Section: Amino Acid Pairingmentioning
confidence: 98%
See 1 more Smart Citation
“…30,31 In addition, the effects of altered peptide lengths (EAR16-II vs. EAR8-II), amino acid arrangements (EAR8-II vs. EAR8-IIa) and side chain hydrophobicity (EAR8-IIa vs. ELR8-IIa) were also investigated. These factors could have impacts on peptide self-assembly, peptide-EPT complexation and their surface properties, 32,33 which may lead to different delivery efficacy and biocompatibility. We explored in detail the relationship between sequence and structure/ property of the new peptides.…”
mentioning
confidence: 99%